Impact of work training and work culture on work productivity - Erina Rulianti; Giri Nurpribadi (Jurnal Mantik, 2023)
The study aims to test the impact of employment training and work culture on work productivity in a company. The data was collected from 66 respondents who were employees of the company. Regression analysis is used to test the research hypothesis. Research results show that work training and work culture have a significant positive impact on work productivity. Employment training plays an important role in improving the skills and knowledge of employees, which can help increase productivity. In addition, a good work culture can boost employee motivation and work spirit, which also contributes to increased work productivity. The study concluded that companies should pay attention to work training and work culture to increase work productivity. Employment training should be aimed at improving the skills and knowledge of employees, while work culture should encourage employee motivation and work spirit. Thus, the company can higher labor productivity and increase its competitiveness in the market.